2019
DOI: 10.1182/blood-2019-125824
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Pitfalls of Stepwise Laboratory Testing for Heparin Induced Thrombocytopenia: Retrospective Review from an Academic Medical Center

Abstract: Introduction: Heparin induced thrombocytopenia (HIT) occurs in up to 5% of adults exposed to heparin due to formation of heparin-dependent antibodies to the heparin/platelet factor 4 (PF4) complex. Patients develop thrombocytopenia and are at risk for severe thrombotic complications. Mortality rates can be as high as 20%, but are often much lower with prompt recognition, cessation of heparin, and treatment with alternative anticoagulants. However, these alternative medications are often both labor-intensive dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Further, PIFA results do not correlate with EIA reactivity. Overall, the data are compatible with a test that yields a positive result approximately 42% of the time (all PIFA studies pooled [10][11][12][13][14][15], with minimal if any association with whether the patient has HIT or not ( Figure 1A), or indeed whether anti-PF4/heparin antibodies detectable by EIA are present or not (Figure 1B). As indicated by the single PIFA PLUSS study, 16 the new test version has similar suboptimal performance.…”
supporting
confidence: 68%
See 4 more Smart Citations
“…Further, PIFA results do not correlate with EIA reactivity. Overall, the data are compatible with a test that yields a positive result approximately 42% of the time (all PIFA studies pooled [10][11][12][13][14][15], with minimal if any association with whether the patient has HIT or not ( Figure 1A), or indeed whether anti-PF4/heparin antibodies detectable by EIA are present or not (Figure 1B). As indicated by the single PIFA PLUSS study, 16 the new test version has similar suboptimal performance.…”
supporting
confidence: 68%
“…Further, these investigators 7 were not able to include in their review an earlier 2007 study we reported, 10 as our results were presented graphically (as ROC curve analyses) without providing the numerical data needed for inclusion in the systematic review. This likely also explains why our joint Hamilton/Greifswald PIFA evaluation (assessing 289 samples, including 25 HIT-positive patients) 10 was not included in a later systematic review of rapid immunoassays by Nagler et al 8 In the meantime, additional data on the PIFA has become available, [12][13][14][15] including two studies 13,14 presented in abstract form at the recent ASH annual meeting (December 2019). We now report the results of our analysis involving the sensitivity and specificity of the PIFA in all English language studies reported to date, [10][11][12][13][14][15] along with a recent study evaluating a modified PIFA, the PIFA PLUSS.…”
mentioning
confidence: 99%
See 3 more Smart Citations